A novel 4-fluorobenzenetelluronic trimethyltin ester: synthesis, characterization and in vitro cytotoxicity assessment. (21st June 2016) - Ma, Chunlin; Liu, Xinglong; Cheng, Shuang; Li, Qianli; Zhang, Rufen
Abstract : A novel 4-fluorobenzenetelluronic trimethyltin ester (Me3 Sn)4 [ p -F-PhTe(μ-O)(OH)O2 ]2 (1 ) has been prepared and structurally characterized, and apoptotic cytotoxicity assessments for A549 cells are made. Abstract : A novel 4-fluorobenzenetelluronic trimethyltin ester (Me3 Sn)4 [ p -F-PhTe(μ-O)(OH)O2 ]2 (1 ) has been prepared and fully characterized using elemental analysis, FT-IR, NMR ( 1 H, 13 C, 119 Sn) spectroscopy, XRD and X-ray crystallography. Structural analysis shows that the complex is crystallized as a Sn4 Te2 molecule, in which an asymmetric four-membered Te2 (μ2 -O)2 unit is situated in the center. The geometry of tellurium is described as a distorted octahedron and for each tin it is described as a distorted tetrahedron. Underlying cytotoxic mechanisms involved in the apoptotic death of A549 cells upon exposure to the complex have been investigated and the results reveal that the anti-proliferative and proapoptotic effects of the complex in A549 cells prominently contributed to the accumulation of ROS, dysfunctional depolarization of the mitochondrial membrane and activation of caspase-3.